Análise do ensino do comportamento de ecoico em gêmeos concordantes para autismo: diferenças encontradas e suas implicações - Mioto, Isabella Lopes (Universidade Federal de São Carlos, 2023)
Current research claims that genetic makeup, together with environmental factors, may contribute to the cause of childhood autism, as they point to evidence of heritability and a higher incidence of autism in families with a history of it. Case studies on twins are scarce in the literature, but fundamental for analyzing the possibility of heritability and the importance of ontogenesis. In its characterization, ASD is marked by abnormalities in social interaction, communication, spoken language and a shallow and stereotyped behavioral repertoire. This impairment in verbal behavior, present in people with autism, is frequently described in the literature. In this audience, one of the main verbal operants that can present a loss in its acquisition is the echoic. In order to understand the functions related to the processes of acquisition of human behavior, it is necessary to study child development and its particularities, especially with atypical children, and, therefore, longitudinal studies with this theme must be carried out. Therefore, the objective of this research was to describe and analyze, in a longitudinal and specific way, the acquisition process of echoic behavior and its prerequisites in twins concordant for autism, identifying the differences that occurred in the learning process and listing possible implications of this learning, bearing in mind that both brothers were submitted to the same protocols, under similar application conditions. For this purpose, the method used was a primary source documentary research. It was verified, retrospective, descriptive and longitudinally, the acquisition of the echoic repertoire and its prerequisite behaviors for learning by children with ASD. The analysis of the reported data confirms the effectiveness of the ABA-based behavioral intervention model for teaching verbal repertoire and strengthens the notion that individualized, structured interventions, with individualized teaching schedules and based on scientific evidence can be applied to teach skills that may favor or improve the quality of life of the individual. In addition, this research presents significant contributions by expanding the data in the literature on behavioral intervention and the acquisition and generalization of verbal behaviors and their prerequisites, in addition to bringing more information to fill the gap present in the literature on behavioral intervention and its repertoires of learning in twins.
Analysis of teaching echoic behavior in twins concordant for autism: differences found and their implications
Keywords: Transtorno do espectro autista; Comportamento verbal; Ecoico; Gêmeos; Autistic spectrum disorder; Verbal behavior; Echoic; Twins; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO